Stygophrynus orientalis sp. nov. (Amblypygi: Charontidae) from Indonesia with the description of a remarkable spermatophore - Seiter, Michael; Wolff, Jonas O. (Zootaxa, 2017)
Here Stygophrynus orientalis sp. nov. is described, a new charontid whip spider from Banggai Island, Indonesia, representing the most eastern record of the genus exceeding the formerly postulated restriction of its distribution western of the Wallace Line. In addition, the third known spermatophore of a Stygophrynus species is presented, which differs remarkably from those previously described from the genus. Finally, the cerotegument structure of the new species is depicted and compared with that of other Charontidae and Charinidae.